Analiza kosztów sztucznego i naturalnego odnowienia dębu w wybranych nadleśnictwach - Kaliszewski, Adam (Leśne Prace Badawcze, 2017)
The aim of the paper is to present the results of a cost analysis for artificial and natural oak regeneration in selected forest districts in Poland. This research was conducted in six forest districts with a high share of natural oak regeneration, located in south-western and central Poland. Altogether 65 plots with artificial and 35 plots with natural regeneration were analyzed based on the extent of silvicultural (weeding, supplementary planting and pre-commercial thinning) and protective measures (chemical and mechanical wildlife damage control, fencing) performed on the regenerated areas for the six years following forest regeneration. An intensity ratio (i.e. a proportion of the area of measures to the area of forest regeneration) as well as the mean unit costs of the measures and mean costs of the measures per hectare of forest regeneration were calculated. The results show that the total costs of silvicultural and protective measures in natural oak regeneration were considerably lower as compared to artificial regeneration. The cumulative average costs during 6 years (without costs of fencing) amounted to 1216 PLN/ha and 6543 PLN/ha for natural and artificial regeneration respectively. Lower costs of natural oak regeneration resulted from the complete lack of expenditures on seedlings and planting, a considerably lower weeding intensity, scarce supplementary planting, and the absence of mechanical wildlife damage control measures. Nonetheless, natural regeneration generated higher costs for pre-commercial thinning due to its higher intensity, earlier initiation, and higher unit costs compared to artificial regeneration, as well as chemical wildlife damage control measures which unit costs were higher by over 50%. However, higher costs of pre-commercial thinning and chemical control measures did not significantly affect the measurable financial benefits of natural regeneration. In conclusion, the matter of financial viability of natural oak regeneration should be explored in more detail over longer time spans.